ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGEMBANGAN UMKM MOCHI DI BARUGA STREET FOOD PALU SULAWESI TENGAH - Desinta Desinta; Jihan Dzalfana; Nur Adha Kausen; Suasa Suasa; Dandan Haryono; Nurhayati Hamid (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This study aims to evaluate the variables that influence the development of micro, small, and medium enterprises (MSMEs) producing mochi at Baruga Street Food in Palu, Central Sulawesi. As public interest, especially among the younger generation, in modern snacks with various flavors continues to grow, MSMEs producing mochi continue to develop. This research uses a qualitative methodology by conducting in-depth interviews and documenting three informants, namely the owners and employees of three mochi MSMEs operating at Baruga Street Food. The results show that relatively stable capital, product quality, service quality, display innovation, and social media-based marketing strategies have been proven to effectively influence the development of mochi MSMEs. However, there are several problems, including variations in the number of customers due to weather, competition between mochi sellers in the same place, and a shortage of raw materials, especially strawberries. In addition, the government provides SMEs with sales facilities and supporting infrastructure. According to this study, the growth of mochi SMEs is highly dependent on the ability of business actors to innovate, maintain quality, and use digital marketing technology.